The Impact of Differentiated Learning on Student Learning Outcomes in Visual Arts Subject at UPT SD Negeri 1 Pinrang - Armiati Armiati; Elihami Elihami; Syawal Sitonda (Universitas Muhammadiyah Enrekang, 2024)
This research investigates the influence of differentiated learning approaches on student learning outcomes in visual arts education at UPT SD Negeri 1 Pinrang. The study employed a quasi-experimental design with pretest-posttest control group methodology, involving 60 fourth-grade students divided into experimental and control groups. The experimental group received differentiated learning instruction tailored to individual learning styles, readiness levels, and interests, while the control group experienced traditional teaching methods. Data collection utilized visual arts performance assessments, student engagement observations, and learning outcome evaluations. Statistical analysis employed paired t-tests and independent sample t-tests to examine within-group and between-group differences. Results demonstrated significant improvements in the experimental group's visual arts learning outcomes, with mean scores increasing from 68.5 to 82.3, compared to the control group's improvement from 67.8 to 71.2. The differentiated learning approach showed particular effectiveness in enhancing creative expression, technical skills, and artistic appreciation among students with diverse learning preferences. Students in the experimental group exhibited higher engagement levels, improved self-confidence in artistic activities, and enhanced collaborative skills during visual arts projects. The findings suggest that differentiated instruction significantly impacts student achievement in visual arts education by accommodating individual learning differences and promoting inclusive educational practices. This research contributes to the growing body of evidence supporting differentiated pedagogy in elementary arts education and provides practical implications for educators seeking to optimize learning outcomes for all students.